Ozone production in a maritime pine forest in water-stressed conditions. (15th January 2019) - Kammer, J.; Lamaud, E.; Bonnefond, J.M.; Garrigou, D.; Flaud, P.-M.; Perraudin, E.; Villenave, E.
Abstract: During two growing seasons of a maritime pine stand, in 2014 and 2015, ozone (O3 ) fluxes have been determined using the eddy covariance (EC) method and compared to the outputs of a big-leaf O3 deposition model including stomatal, cuticular and soil pathways. The model developed in this study generally allowed to properly reproduce the measured ozone deposition. Ozone fluxes showed a strong reduction during two water stressed periods in September 2014 and July 2015. The model partly explain this fall due to the reduction of stomatal deposition. Despite this stomatal closure, measured O3 fluxes presented systematically lower negative values than the model outputs, and sometimes even positive values around midday during periods marked by strong water stress. In other words, the difference between observed and modelled O3 fluxes (hereinafter referred to as the residual O3 flux) is systematically positive on daytime during these water-stressed periods. This positive residual flux traduced the existence of an O3 source below the flux measurement level, responsible for positive fluxes that counterbalance deposition fluxes. We developed an O3 production module based on a terpene emission algorithm and an OH concentration proxy, to try to explain the observed ozone production. As this parametrisation allowed us to reproduce well the daily and inter-daily dynamics of the residual O3 flux, it confirms that the latter actually resulted from O3 production processes. This ozone production is here highlighted for the first time using O3 fluxes measurements by the EC method. The chemical reactions possibly involved in O3 production processes in this maritime pine forest have been discussed and different mechanisms are proposed, based on peroxy radicals chemistry or stress-induced BVOCs. Highlights: Ozone (O3 ) fluxes have been measured and modelled over a maritime pine stand. Two water-stressed periods provoked a strong reduction of O3 deposition. Comparison between modelled and measured O3 fluxes highlighted an O3 production during water-stressed periods. O3 production seems to be related to BVOCs photochemistry.